If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(1 + -1x) = 0 (1 * 2 + -1x * 2) = 0 (2 + -2x) = 0 Solving 2 + -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -2x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -2x = 0 + -2 -2x = 0 + -2 Combine like terms: 0 + -2 = -2 -2x = -2 Divide each side by '-2'. x = 1 Simplifying x = 1
| 9+5w-14w=12-6 | | 3(x+4)=6(x-2) | | -4y^3-8xy^4=-4y^4(1+2xy) | | A-13.4=2.6 | | 100x-200=50x-5 | | 3m+6-25=-22 | | 10(-3-2t)+10-2(6+13)=0 | | (-2x)(x+3)+(3x)(x-2)=-27 | | 0.10(100)+15=0.15(100)+x | | 45-5n+5= | | f(x)=5x^2-x+20 | | 8x^2-20x+25=0 | | x+122=2x+80 | | -29=5w-4 | | 4(2x-3)+7=x+5+x | | -4(5x+10)=-180 | | 0=12x^2-4x^3 | | 11+17-6x=2 | | 3x+14=94 | | 2x^2+4+5x=4 | | 4-3t+10+10t=0 | | x-(-28)=-48 | | -5(1+a)-6a=-8a+19 | | x-6=15+8x | | 0=24x-12x^2 | | 3x+5x-3=8x | | -3x-184=59-12x | | -56+h-8= | | 2.4=(m+4) | | -7(2+2x)=-70 | | 4x+3(-2x-7)=-7 | | 7a+10a+7a+12a=360 |